Role Playing Method on Arabic Speaking Skill (Maharah Kalam) - Basri, Dewi Jumrahwati; Hasmawati, Hasmawati; Ulum, Fatkhul (Universitas Negeri Makassar, 2024)
Abstract. The research is a pre-experiment quantitative research with one group pre-test post-test design which aims to determinate the effectiveness of Role Playing method on Arabic speaking skills (Maharah Kalam) of fifth grade students of Madrasah Ibtidaiyah Fatthu Rahman Makassar. The population and samples in this study were all fifth grade students of Madrasah Ibtidaiyah Fatthu Rahman Makassar which amounted to 24 students using total sampling technique. The basis of the research results was obtained by giving oral pre-test and post-test with the material